Study on the Adsorption Process of Monoethanolamine (MEA) Wastewater Using Activated Carbon and Treated Rice Husk - Noradlinnaini, Muhamad (2013)
Monoethanolamine (MEA) is versatile bifunctional molecules compound which by the reaction it behaves like alcohol and Amine but Amine group usually exhibit the greater activity. MEA was always used as a gas stream scrubbing agent to remove carbon dioxide (CO2) from flue gas known as stripping process. During the oil processing, some MEA with other wastes enter to industrial wastewater. This study was conducted to suggest the best method of treating the MEA wastewater in order to meet the potable quality standards and suited for reused of MEA.The method of treatment is by using adsorption process with two types of adsorbent which are treated rice husk, and activated carbon. Two parameters were manipulated to get the optimum value of removing oil, chemical oxygen demand (COD) and amine concentration that are adsorbent dosage and mixing speed. From the results we can see the oil residue and COD decreased while MEA concentration wastewater remains the same. Activated carbon became the most effective adsorbent for the adsorption process with up to 43.57% oil content removal and 66.81% COD reduction. Meanwhile, treated rice husk showed lower efficiency performance throughout this process with 37.83% oil removed and 53.32% COD reduction. MEA concentration remain constant for both adsorbent.